2021
DOI: 10.1177/20563051211043906
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Social Capital and Loneliness for the Elderly: The Moderator Role of Line and Facebook Use

Abstract: Social media has become a vital source of communication for older adults, but its impact is still an ongoing debate. This study investigated the moderating effect of Line and Facebook use on social capital and loneliness in older adults, aged 55 or more, using data obtained from the 2018 Taiwan Communication Survey (TCS). Results from binary logistic regression indicated that older adult users of Line have a lower possibility of being lonely than those who do not use Line. Consistent with past studies, this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 60 publications
(117 reference statements)
0
6
0
3
Order By: Relevance
“…De forma general, los social media mejoran el capital social de las personas mayores (Hsu et al, 2021;O'Brien et al, 2021;Yu, 2020;Yu et al, 2018), impactando positivamente en su autonomía y su bienestar (Jones et al, 2015;Llorente-Barroso et al, 2021;Simons et al, 2021;Zhang et al, 2021). Desde una perspectiva ciudadana, las redes sociales permiten al colectivo senior la posibilidad de realizar un intercambio de ideas dentro de una comunidad virtual (Xu, 2022).…”
Section: El Valor De Los Recursos Tecnológicos Y Digitales Para Los S...unclassified
See 1 more Smart Citation
“…De forma general, los social media mejoran el capital social de las personas mayores (Hsu et al, 2021;O'Brien et al, 2021;Yu, 2020;Yu et al, 2018), impactando positivamente en su autonomía y su bienestar (Jones et al, 2015;Llorente-Barroso et al, 2021;Simons et al, 2021;Zhang et al, 2021). Desde una perspectiva ciudadana, las redes sociales permiten al colectivo senior la posibilidad de realizar un intercambio de ideas dentro de una comunidad virtual (Xu, 2022).…”
Section: El Valor De Los Recursos Tecnológicos Y Digitales Para Los S...unclassified
“…Por ello, se precisa una revisión de los actuales modelos de e-government y de e-commerce para adaptarlos a las necesidades de accesibilidad de los diversos perfiles de adultos mayores (Sánchez-Valle, Llorente-Barroso et al, 2022;Viñarás-Abad et al, 2022). En este proceso de actualización y desarrollo de soluciones de innovación tecnológica para seniors, conviene implicar a las propias personas mayores (Butt et al, 2022) para garantizar que puedan aceptarlas como accesibles y verdaderamente útiles (Ansello & Eustis, 1992;Astell et al, 2020;Hsu et al, 2021;Jones et al, 2015;Llorente-Barroso et al, 2021;O'Brien et al, 2021;Simons et al, 2021;Yu, 2020;Yu et al, 2018;Zhang et al, 2021). De modo análogo, las TIC se han catapultado como herramientas esenciales para la inclusión de las personas con discapacidad (Lin et al, 2018), al facilitar su participación en la sociedad (Jaeger, 2012;Lord et al, 2014;Williams, 2019) y permitirles una conexión con las administraciones públicas y los gobiernos (Sylvester & McGlynn, 2010).…”
Section: Conclusiones Y Discusiónunclassified
“…It is expected to have the oldest population among OECD countries in terms of average age in the 2050s (OECD, 2023), causing various societal and economic challenges. Humans go through many changes as they age, and loneliness is one of the most widespread problems faced by older people worldwide (Hsu et al, 2021). Studies reported that 25% to 29% of older people in the U.S. experienced loneliness (Ong et al, 2016), 28.1% in China (Yu et al, 2021), 18.7% to 24.2% in eastern European countries (Surkalim et al, 2022), and 29.1% in South Korea (Kim et al, 2022).…”
Section: Loneliness and Social Media Use Among Older Adultsmentioning
confidence: 99%
“…According to the Spring 2022 Global Attitudes Survey, 70% of older adults in Korea reported using social media, followed by 69% in Australia, 66% in Israel, 63% in Canada, Singapore, and Sweden, 60% in Japan and the United States, 56% in Greece and Malaysia, 53% in Italy and Spain, 51% in Netherlands, 50% in Belgium, and less than 50% in France, Hungary, Poland, and the United Kingdom (Pew Research Center, 2022). As the use of social media among older adults’ population is increasing, the potential of social media as a source of social connection appears to be particularly important for older adults (Hsu et al, 2021). However, most studies on social media and mental health focus on younger adults (Hsu et al, 2021; Masur, 2021), and there is limited research on the effects of social media use on the loneliness of older adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation